GENETICS OF AUTISM SPECTRUM DISORDERS - Pomohaibo, V.M.; Berezan, O.I.; Petrushov, A.V. (World of Medicine and Biology, 2016)
The review of research results of genetic mechanisms of autism spectrum disorders is carried out. According to current ideas there are two extreme forms of autism: a form of direct genetic definiteness of disorder and a form of hereditary tendency to pathology between which there are various intermediate illness forms. In case of tendency to a disease the significant role in its development is played by provocative factors of environment, the variety and the number of which is constantly increasing in the modern techno genetic world. Genetic component takes an important role in autism etiology, because the coefficient of its heritability can reach up to 90%. The mutations of certain genes are the reason of nearly 15% of cases of autism, typical for particular families. The other cases are polygenic. Over 100 genes connected with autism have been determined so far. About 60% of them are dominant and about 40% are recessive. These genes are found practically in all chromosomes, except the 13th, 18th, 21st and Y-chromosome. Their greatest number is in the X-chromosome (45) and the 17th chromosome (7); in other autosomes – on average there are about 3 genes.